Redesenhando o currículo do ensino médio: O caso do ProEMI na escola Educandário Oliveira Brito - Euclides da Cunha/BA - Machado, Anny Karine Matias Novaes (2016)
Historically high school consists in a level of greater complexity in the public policies’ elaboration. It is marked by a long process of undefined identity, whose fluctuations involve a propaedeutic model destined to continue studies in higher education and professionals that are directed to the working classes. Nowadays, the high school reformulation policies takes the curriculum as focus of change and seek to overcome this structural duality (KUENZER, 2010) which comes from an integrated training that are structured by axis of work as an educational principle, science and technology as a mode of understanding social and physical transformations and culture as ethics and esthetics’ productions of societies. In this scenario, the “Programa Ensino Médio Inovador – ProEMI” (which means High School Program Innovator) established by Decree 971 of 9 October 2009 was born with the goal of enabling the redesign of the school curriculum in order to overcome the educational differences; universalizing access and permanence; consolidate the identity and diversity, to offer significant learning; integrate and articulate knowledge of interdisciplinary and recontextualisation from diverse educational activities inserted in macro fields. In this sense, this research conducted in Educandário Oliveira Brito school in Euclides da Cunha City, located in state of Bahia, Brazil, aimed to understand how the institution has been in recontextualisation proposed by ProEMI as curriculum reform and how it has been focused in daily practices; the organizational dimensions of culture and school schedule; and the access and permanence of young people in schoolas well. About the study of ethnographic case, the construction of the “corpus” came from participant-observation, document analysis, interviews with the coordinators that are responsible for the program, including a manager and seven of the eight teachers that are responsible for the workshops. The option for the analysis of recontextualisation of processes consists in Bernstein (1990, 1996) and Lopes (2008), Goodson (2013), founded the diagnosis of educational changes, Ball (2001, 2006) and Moreira (2012, 2012a, 2012b ) offered subsidies for reflection on educational policies and educational transfer - respectively and finally Bardin (1995) that brings the analysis of enunciation methods of understanding the data collected. Therefore, it became apparent that the recontextualisation of processes from ProEMI occurred in hybrid ways, translated from the actual model of the American high school, reframed by the subjects in the school routine. It also showed a proposal of inflexibility, in that the redesign of the school curriculum includes only one model of pedagogical activity: the workshop. The lack in teacher training processes unfortunately involves the whole school collective. Finally, the examination of questionnaires that was given to students who attend the workshop reflects on the category of youth and the importance of youth participation and the engagement of all subjects in school changes.